La Gestion Des Finances Publiques, Comment Gagner En Efficacite ? - Ameur, Sara (European Scientific Journal, ESJ, 2017)
In a field as sophisticated as public finances, which concerns the lives of our fellow citizens and their future, it would be risky to want to reform without a deep approach to decrypt the management of public finances... It is true that it is simpler and even simplistic, to make the economic and financial situation bear the responsibility for the difficulties of public finances, but in order to remedy the main problems it is necessary to undertake structural reforms by the help of scientific research; And by conducting an evaluation of the effectiveness of public financial management.